Pengaruh Pijat Bayi Dengan Tumbuh Kembang Bayi - Yunri merida; Fatya Nurul Hanifa (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
Background: According to Pitre (2021) Baby massage is a routine care for babies that has been known for a long time by the community and also to express the affection between parents and their children through skin touch which has a tremendous impact. Baby massage is often referred to as stimulus touch. Objective: To determine the effect of baby massage on infant growth and development. Methods: The type of research used in this research is Pre-Experimental Design in the form of Intact Group Comparison. The population of this study were all 60 babies aged 6-12 months in PMB Hana. The sampling technique used in this research is total sampling. The statistical test used is the Chi Square Test. Result: The result of this research is that there is an effect between baby massage and infant growth and development at PMB Hana with P-Value <0.0001 Suggestion: There is a need to increase education about baby massage for mothers who have babies aged 6-12 months.